Axialy chiral n-(o-aryl)-2-thioxo-oxazolidine-4-one and rhodanine derivatives: enantiomeric separation and determination of racemization barriers - Yılmaz, Esra Müjde. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2008., 2008)
In this study, sterically hindered 5,5-dimethyl-3-(o-aryl)-2-thioxo-4-oxazolidinones, 5,5-dimethyl-3-(o-aryl)-2-thioxo-4-thiazolidinones and 3-(o-aryl)-2-thioxo-4- thiazolidinones(rhodanines) have been synthesized as racemates by either the reaction of oaryl isothiocyanates with α-hydroxyisobutyrate or by treatment of o-arylisothiocyanates with the correponding thioglycolic acid ethyl ester. The 5,5-dimethylrhodanines have been synthesized according to Modified Kaluza synthesis. Chirality of the compounds has been proven by the presence of diastereotopic methylene protons or methyl groups on C-5 of the heterocyclic ring detected by 1H NMR or 13C NMR spectroscopy. The enantiomers of the synthesized compounds have been resolved or enriched micropreparetively on chiralpak AD-H column, packed with amylose tris-(3,5-dimethyl phenyl)carbamate. The activation barriers for interconversion between the enantiomers have been determined by either temperature dependent NMR or by thermal racemization followed by enantioresolution on a chiral sorbent via HPLC. The activation barriers to rotation around C-N bond showed a linear increase with the van der Waals radii of the ortho-halogen substitutents. Absolute conformations have been determined by analysis of NMR spectra of Nnaphthyl substituted derivatives of the series in the presence of the chiral auxiliary (S)-(+)- 1-(9-antryl)-2,2,2-trifluoro ethanol ((S)-TFAE). Plausible diastereomeric association models between the enantiomers of the compounds 3-(α-naphthyl)-2-thioxo-4- ii thiazolidinone and 3-(α-naphthyl)-2,4-thiazolidinedione and the chiral auxiliary (S)-TFAE have been proposed. Enantiodifferentiation of 3-aryl-2-thioxo-4-oxazolidinones by NMR was also studied by using a dirhodium tetracarboxylate complex as the chiral auxiliary. Determination of relative conformations of the series have also been attempted by applying the dirhodium method to the enantiomerically enriched samples, however this could not be achieved.
Keywords: Chirality.; Enantiomers.; Stereochemistry.; Organic compounds -- Synthesis.